The Effect of Excessive Foreign Debt on the Economic Climate – the Example of Latin America - Krupa, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article examines excessive indebtedness at the country level. The study covers the years 1975–1995, during which this problem affected particularly medium-developed countries and the lack of its solution implied a threat of a global economic crisis. This was one of the most serious global economic crises and global debt crises to have occurred in the general history of finance, seriously destabilising economies and the political situation. The political sphere also to some extent conditioned the procedure for its solution.